Eyewitness to World War II : unforgettable stories and photographs from history's greatest conflict - Hyslop, Stephen G.; Kagan, Neil.; Hyslop, Stephen G. (Stephen Garrison), 1950- (Washington, D.C. : National Geographic Society, 2012)
Personal writings and recollections of Roosevelt, Hitler, and Patton, as well as letters composed by soldiers at battle and diaries of women serving in the military at home, present an absorbing narrative that tells the entire history of the war from several perspectives.
Foreword / by Hugh Ambrose -- Through the lens : A world gone mad -- Seven days in December -- Through the lens : Home front U.S.A. -- Striking back at Japan -- Through the lens : Face-off in the desert -- War in the Mediterranean -- Through the lens : A war of wills -- Island fighting -- Through the lens : The battle of the Atlantic -- Through the lens : Air war over Europe -- Victory over Germany -- Through the lens : Holocaust -- Victory over Japan.
Includes index.
Includes bibliographical references and index.
104989
Keywords: Personal narratives, American; Pictorial works; World War II -- 1939-1945 -- United States; Personal narratives -- American; Pictorial works